Estratégias na identificação e caracterização de potenciais antifúngicos e seus alvos em Paracoccidioides brasiliensis - CARVALHO, Patrícia Fernanda Zambuzzi (2010)
The termodimorphic fungus Paracoccidioides brasiliensis is the etiological agent of paracoccidioidomycosis (PCM), a systemic human mycosis geographically distributed in Latin America, being the eighth most common cause of death among chronic infections. PCM is acquired by inhalation of fungal propagules, which reach the lungs and is disseminate through the bloodstream and/or lymph to all parts of the body. The treatment of PCM is long, starting with a dosage of aggressive antifungal agents, extending for months or years. Resistance to antimicrobial drugs may limit the ability of effective treatment of patients, interfering with therapeutic efficacy. Thus, it is necessary to discover and develop new antifungal agents. Plants compounds have a great structural diversity, many of which are models for the synthesis of a vast number of drugs. The action of the oenothein B compound, purified from leaves of Eugenia uniflora, a plant from the Brazilian Savannah, was evaluated on growth, viability and expression of P. brasiliensis genes. The compound interfered with cell morphology and inhibited the transcripts of β-1- 3-glucan synthase. The synergistic effect between oenothein B and drugs used to treat PCM (amphotericin B, itraconazole, Sulfamethoxazole and Trimethoprim-Sulfamethoxazole Combination) was evaluated in this study by the method of sensitivity on plates. The highest inhibition of the fungal growth was observed in association of oenothein B with Trimethoprim-Sulfamethoxazole Combination, followed by amphotericin B, itraconazole and sulfamethoxazole, respectively. Representational Difference Analysis (RDA) was also performed to elucidate the mechanism of action of oenothein B in P. brasiliensis. We identified 463 ESTs up regulated and 121 ESTs down regulated after 90 min of incubation of P. brasiliensis yeast cells with the compound. After 180 min incubation 301 ESTs up regulated and 143 down regulated were identified. The ESTs were classified according to their functional categories using the program Blast2GO. The analysis indicated the presence of transcripts with functions related to cell wall and membrane, transcription factors and hypothetical proteins. In this study, we evaluated also the characteristics of the malate synthase (Pbmls) cDNA, regulation of Pbmls gene expression, and enzymatic activity of the MLS protein of P. brasiliensis (PbMLS), isolate Pb01. The cDNA contains 1617 bp, which encodes a protein of 539 amino acids. The protein has the signature of the MLSs, residues essential for catalytic activity and addressing signal for peroxisomes, PTS1. The high level of Pbmls transcript observed in the presence of 2C sources suggests that in P. brasiliensis, the primary regulation of carbon flux into glyoxylate cycle was at the level of the Pbmls transcript. Transcript analysis, protein levels and enzymatic activity in the presence of different carbon and nitrogen sources suggest that PbMLS acts in both pathways: in glyoxylate cycle, when 2C sources are used, and in alantoin degradation pathway, when proline is used as nitrogen source, or when oxalurate is used to induces genes from pathway.